Etyczne konsekwencje zaniku świadomości bycia śmiertelnym - Kopania, Jerzy (Zeszyty Naukowe Centrum Badań im. Edyty Stein, 2012)
Max Scheler argued that the consciousness of being mortal was replaced by the knowledge of being mortal in the modern period, so now human beings only knowthat they are mortal. The goal of the article is to prove that this replacement has greatethical consequences, i.e. it is mainly the cause of the dominance of utilitarian ethics in Western civilization.